Two promoter polymorphisms in TBX22 are associated with the risk of NSCLP in Indian women. Issue 4 (October 2015) - Gurramkonda, Venkatesh B.; Hussain, Syed A.; Murthy, Jyotsna; Lakkakula, Bhaskar V.K.S.
<x xml:space="preserve">Abstract</x> The aetiology of nonsyndromic cleft lip with or without cleft palate (NSCLP) is complex and involves both genetic and environmental risk factors. Classical research has shown that growth and patterning of the developing palatal shelves depend on epithelial–mesenchymal interactions. Expression of several signalling molecules and transcription factors in the anterior palate during early palate development has been documented. TBX22 encodes a T-box containing transcription factor and mutations in this gene are responsible for X-linked cleft palate and ankyloglossia. In the present study, we analysed two TBX22 promoter rs7055763 and rs41307258 single-nucleotide polymorphisms (SNPs) in 173 patients with NSCLP and 176 normal controls of south Indian origin using Kbioscience KASPar chemistry, which is a competitive allele-specific PCR SNP genotyping system. As the SNPs are located on chromosome X, the association analysis was carried out separately in men and women. Significant associations of rs7055763 (P=0.034) and rs41307258 (P=0.022) with NSCLP were found only in women. Both polymorphisms increased the risk for NSCLP in the heterozygous and homozygous variant state, but this was not significant. Both SNPs were not associated with a risk for NSCLP in men. Pair-wise linkage disequilibrium between rs7055763 and rs41307258 was strong and significant (D′=0.97 and r2=0.77). Only three haplotypes were observed with an estimated frequency more than 5%. Haplotype AA, which carries both mutant alleles (rs7055763 A – rs41307258 A), was significantly associated with an increased risk of NSCLP in women, but not in men. Our study showed a significant role of TBX22 promoter polymorphisms (rs7055763 and rs41307258) in the pathogenesis of NSCLP and reinforces the previous findings of a strong link between X-linked genes and orofacial clefts.